Collaborative planning? Not yet seen in Poland. Identifying procedural gaps in the planning system 2003–2023 - Mironowicz, Izabela; Ciesielski, Michał (Bulletin of Geography. Socio-economic Series, 2024)
Collaborative planning aims to increase the legitimacy of decision-making in spatial development. In this approach, planning involves debate and engagement in discourse, and participation and interaction between actors are thus at the heart of the planning process. This article examines whether the planning system in Poland as defined for the period 2003–2025 provides a level of participation and deliberation and other qualities that together allow it to be classified as a collaborative model. The legal procedures in the most commonly used planning instruments are therefore analysed in detail to determine whether they provide honest, open, equal and transparent access to the decision-making process to all stakeholders. The analysis reveals numerous deficiencies in the planning procedures that undermine the collaborative nature of spatial planning in Poland. The study summarises the experience of twenty years of spatial planning practice in Poland and provides a useful starting point for assessing the new planning system that has gradually been being implemented since 2023.